The Economics of Internet of Things: An Information Market System - Vadlamudi, Siddhartha (Asian Business Review, 2021)
The Internet of Things (IoT) is one of the leading forces in modern-day technology. The concept has been proposed to be a new way of interconnecting a multiplicity of devices and rendering services to a variety of applications. According to the industry’s insiders, IoT will make it possible to link transport, energy, smart cities, and healthcare together. The purpose of this paper is to understand the economics of the Internet of Things. It is meant to shed light on how world IoT applications can affect the information market. When every sector and industry of the world has been connected via this technology, what will become of the ICT niche? The information economic approach is currently being adopted and presented with its possible applications in IoT. Firstly, this paper reviews the kinds of economic models that have been designed for IoT services. Secondly, it focuses on the two major subject matters of information economics that are critical to IoT. While one considers the value of the information itself, the other addresses information with good pricing. Lastly, the paper proposes a game-theoretic model to examine the price competition of IoT-based services. We take a look at how these two sectors will fare against each, both at full capacity.